Molecular Docking of Michelia alba Leaves Active Compounds Against Human Epidermal Growth Factor Receptor 2 (HER-2) - Isman, Felysia; Pratama, Paundra; Fadlan, Arif (Al-Kimia, 2022)
Breast cancer characterized by overexpression of the human epidermal growth factor receptor-2 (HER-2) and is a deadly disease worldwide. Chemotherapy with drugs targeting HER-2 is less effective and shows various drawbacks. This study aimed to study anticancer potential of active compounds contained in Michelia alba through molecular docking against HER-2. The molecular docking study was performed toward HER-2 receptor (PDB: 3PP0) containing 30Q native ligand with MCULE. The results showed that cis-linalool oxide, trans-linalool oxide, linalool, β-elemena, α-humulene, and nerolidol contained in M. alba leaves had lower docking scores than quercetin as control. Nerolidol showed the lowest docking score among all compounds. The active compounds in the leaves of M. alba have the potential as a HER-2 inhibitor in silico.